Diabetes and smoking are associated with dynapenic abdominal obesity in patients with chronic kidney disease: a cross-sectional study - Alessandra Fortes Almeida-Menezes; Maria Ester Pereira da Conceição-Machado; Maria Helena Lima Gusmão; Lílian Barbosa Ramos; Thais Vitorino Neves do Nascimento; Magali Teresópolis Reis Amaral; Jairza Maria Barreto-Medeiros (São Paulo Medical Journal)
ABSTRACT BACKGROUND: No study has reported about the prevalence and factors associated with dynapenic abdominal obesity in patients with pre-dialysis chronic kidney disease (CKD). OBJECTIVE: Evaluation of the prevalence of dynapenic abdominal obesity and its relationship with sociodemographic, lifestyle, clinical, and nutritional variables in patients with CKD not dependent on dialysis. DESIGN AND SETTING: A cross-sectional study was conducted at the Nutrition and Nephropathy Outpatient Clinic (public service) in Bahia, Brazil. METHODS: This cross-sectional study was conducted on 102 patients of both sexes, aged ≥ 20 years. Dynapenic abdominal obesity (DAO) was defined as the simultaneous presence of dynapenia (handgrip strength less than the first tertile of the sample itself, according to sex and age) and increased waist circumference. Differences between groups with and without DAO were assessed using the Student’s Mann–Whitney t-test, Pearson’s chi-square test, or Fisher’s exact test. Associations were tested using bivariate and multivariate models with Poisson regression to calculate the prevalence ratio and 95% confidence intervals (PR; 95% CI). RESULTS: The mean age of the patients was 58.7 (standard deviation = 11.69); 50.5% were male, 51.6% were elderly, 41.8% had diabetes, 5.5% were smokers, 58.2% were abdominally obese, and 38.5% were dynapenic. DAO was identified in 18.7% of participants and was associated with diabetes mellitus (PR = 2.8; 95% CI = 1.12-6.99) and smoking (PR = 3.22; 95% CI = 1.16-8.96). CONCLUSION: Non-dialysis dependent patients with CKD showed a significant prevalence of DAO associated with smoking and diabetes mellitus.